2013
DOI: 10.1377/hlthaff.2013.0067
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Visits After Surgery Are Common For Medicare Patients, Suggesting Opportunities To Improve Care

Abstract: Considerable attention is being paid to hospital readmission as a marker of poor postdischarge care coordination. However, little is known about another potential marker: emergency department (ED) use. We examined ED visits for Medicare patients within thirty days of discharge for six common inpatient surgeries. We found that these visits were widespread and showed extensive variation across facilities. For example, 17.3 percent of these patients experienced at least one ED visit within the postdischarge perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 39 publications
0
67
2
2
Order By: Relevance
“…To place findings in perspective in other settings, Tang et al (26) showed that rates of ED use in the general population increased from 35 to 39 visits per 100 patient-years between 1997 and 2007, with increased rates among underserved Medicaid patients. A national study of Medicare patients receiving surgery (including percutaneous coronary intervention, hip fracture repair, and coronary artery bypass grafting) reported a 30-day ED visit rate of 17% (14). A 2013 study using the SIDs found that 40% of 30-day acute care encounters after hospital discharge were to an ED (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To place findings in perspective in other settings, Tang et al (26) showed that rates of ED use in the general population increased from 35 to 39 visits per 100 patient-years between 1997 and 2007, with increased rates among underserved Medicaid patients. A national study of Medicare patients receiving surgery (including percutaneous coronary intervention, hip fracture repair, and coronary artery bypass grafting) reported a 30-day ED visit rate of 17% (14). A 2013 study using the SIDs found that 40% of 30-day acute care encounters after hospital discharge were to an ED (10).…”
Section: Discussionmentioning
confidence: 99%
“…However, controversies exist regarding the exact interpretations of the use of acute care services and the correlation with quality of care (7,(11)(12)(13). Health care delivered through the ED can be associated with lower quality of care, higher costs, and lack of coordinated care (14,15). In the context of kidney transplantation, McAdamsDemarco et al (16) documented a 31% incidence of 30-day hospital readmissions.…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S., the Centers for Medicare and Medicaid Services (CMS) recently implemented the hospital readmission reduction program (Centers for Medicare and Medicaid Services, 2014) and funded implementation of care coordination interventions (Brock et al, 2013; Voss et al, 2011), based on evidence that readmissions can be prevented with proper transitional support and discharge planning (Coleman et al, 2006; Leppin et al, 2014). Use of emergency departments (ED) could also indicate poor transitions following inpatient care (Baier et al, 2013; Kocher et al, 2013), but has received less attention from policy makers and is not currently monitored as a hospital quality metric. However, previous literature has highlighted many complex patient-level characteristics that may contribute to risk for readmissions and ED visits, such as patient age, gender, or socioeconomic status (Amarasingham et al, 2010; Arbaje et al, 2008), which may not be modifiable characteristics within the control of hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…High rates of 30-day readmission may also indicate poor integration of the health care delivery system, one in which care is poorly coordinated across settings. 16,17 Similarly, post-discharge emergency department visits, which account for about 40% of all acute post-discharge care encounters 8 and contribute a meaningful share of hospital spending, 1,18 have also been proposed as a novel marker of inadequate care coordination. 7,8,18 A portion of all-cause hospital readmissions and post-discharge emergency department visits are deemed preventable.…”
mentioning
confidence: 99%
“…16,17 Similarly, post-discharge emergency department visits, which account for about 40% of all acute post-discharge care encounters 8 and contribute a meaningful share of hospital spending, 1,18 have also been proposed as a novel marker of inadequate care coordination. 7,8,18 A portion of all-cause hospital readmissions and post-discharge emergency department visits are deemed preventable. 4,5,19,20 High population rates of such events represent opportunities to improve care and use health care resources more efficiently.…”
mentioning
confidence: 99%